Retinoid-related Orphan Receptors (RORs): Roles in Cellular Differentiation and Development - Jetten, Anton M. (2006)
Retinoid-related orphan receptors RORα, −β, and −γ are transcription factors belonging to the steroid hormone receptor superfamily. During embryonic development RORs are expressed in a spatial and temporal manner and are critical in the regulation of cellular differentiation and the development of several tissues. RORα plays a key role in the development of the cerebellum particularly in the regulation of the maturation and survival of Purkinje cells. In RORα-deficient mice, the reduced production of sonic hedgehog by these cells appears to be the major cause of the decreased proliferation of granule cell precursors and the observed cerebellar atrophy. RORα has been implicated in the regulation of a number of other physiological processes, including bone formation. RORβ expression is largely restricted to several regions of the brain, the retina, and pineal gland. Mice deficient in RORβ develop retinal degeneration that results in blindness. RORγ is essential for lymph node organogenesis. In the intestine RORγ is required for the formation of several other lymphoid tissues: Peyer’s patches, cryptopatches, and isolated lymphoid follicles. RORγ plays a key role in the generation of lymphoid tissue inducer (LTi) cells that are essential for the development of these lymphoid tissues. In addition, RORγ is a critical regulator of thymopoiesis. It controls the differentiation of immature single-positive thymocytes into double-positive thymocytes and promotes the survival of double-positive thymocytes by inducing the expression of the anti-apoptotic gene Bcl-X(L). Interestingly, all three ROR receptors appear to play a role in the control of circadian rhythms. RORα positively regulates the expression of Bmal1, a transcription factor that is critical in the control of the circadian clock. This review intends to provide an overview of the current status of the functions RORs have in these biological processes.